2010
DOI: 10.1016/j.virol.2010.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome and genetic characteristics of SRV-4 isolated from cynomolgus monkeys (Macaca fascicularis)

Abstract: At least 5 serotypes of exogenous simian retrovirus type D (SRV/D) have been found in nonhuman primates, but only SRV-1, 2 and 3 have been completely sequenced. SRV-4 was recovered once from cynomolgus macaques in California in 1984, but its genome sequences are unknown. Here we report the second identification of SRV-4 and its complete genome from infected cynomolgus macaques with Indochinese and Indonesian/Indochinese mixed ancestry. Phylogenetic analysis demonstrated that SRV-4 was distantly related to SRV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…1A,B). It is present in the SHAPE-validated (Sonigo et al 1986), M11841.1 (Power et al 1986), AF126467.1 (Marracci et al 1995), FJ979638.1 (Zao et al 2010), and AB611707.1 (Takano et al 2013), respectively. structure of the gRNA (Fig.…”
Section: Sl1 Sl2 and Sl3 Are Present In Spliced As Well As Grnasmentioning
confidence: 99%
“…1A,B). It is present in the SHAPE-validated (Sonigo et al 1986), M11841.1 (Power et al 1986), AF126467.1 (Marracci et al 1995), FJ979638.1 (Zao et al 2010), and AB611707.1 (Takano et al 2013), respectively. structure of the gRNA (Fig.…”
Section: Sl1 Sl2 and Sl3 Are Present In Spliced As Well As Grnasmentioning
confidence: 99%
“…Extensive investigations revealed that this illness was caused by an infection with an SRV/D known as simian retrovirus type 4 (SRV-4) (5; M. Okamoto et al, unpublished data). SRV-4 has been reported to be distantly related to other SRV/Ds, including SRV-1, -2, -3, -5, -6, and -7; e.g., the previously isolated SRV-4 showed genome sequence similarities of 78, 76, and 74% to SRV-1, -2, and -3, respectively (6). Although there is more than 80% amino acid sequence identity between Gag, Prt, and Pol of SRV-4 and SRV-1, -2, or -3, the Env sequence of SRV-4 is relatively diverse (67 to 74%) compared to other SRV/Ds (6).…”
mentioning
confidence: 99%
“…SRV-4 has been reported to be distantly related to other SRV/Ds, including SRV-1, -2, -3, -5, -6, and -7; e.g., the previously isolated SRV-4 showed genome sequence similarities of 78, 76, and 74% to SRV-1, -2, and -3, respectively (6). Although there is more than 80% amino acid sequence identity between Gag, Prt, and Pol of SRV-4 and SRV-1, -2, or -3, the Env sequence of SRV-4 is relatively diverse (67 to 74%) compared to other SRV/Ds (6). Although SRV-4 asymptomatically infects cynomolgus monkeys (7), SRV-4 infection of Japanese macaques has not been reported to date.…”
mentioning
confidence: 99%
“…Additionally, SRV-T, SRV-6 and SRV-7, have been identified, based on the results of phylogenetic analyses (Hara et al, 2005;Nandi et al, 2000Nandi et al, , 2006. SRV-T was reported as a virus strain of SRV-4 based on sequencing analysis (White et al, 2009;Zao et al, 2010).Only one SRV virus strain, D2/RHE/OR, has been isolated from a Japanese monkey (Macaca fuscata) at the Washington National Primate Research Center (Giddens et al, 1985). The D2/RHE/OR and closely related SRV-2 strains (SRV-2B) have also been identified in endemic infections of pig-tail monkeys (M. nemestrina), cynomolgus monkeys (M. fascicularis) and rhesus monkeys (M. mulatta) in the Washington and Oregon National Primate Research Center (Bryant et al, 1986;Grant et al, 1995;Hefti et al, 1983;Marracci et al, 1995 Marracci et al, , 1999 PhilippStaheli et al, 2006;Stromberg et al, 1984).…”
mentioning
confidence: 99%